The Effects of Domestic Climate Change Measures on International Competitiveness - Kee, Hiau Looi (2012)
Under the Kyoto Protocol, industrialised countries (called Annex I countries) have to reduce their combined emissions to 5 per cent below 1990 levels in the first commitment period of 2008-12. Efforts to reduce emissions to meet Kyoto targets and beyond have raised issues of competitiveness in countries that are implementing these policies, as well as fear of leakage of carbon-intensive industries to non-implementing countries. This has also led to proposals for tariff or border tax adjustments to offset any adverse impact of capping CO2 emissions. In this paper we examine the implications of climate change policies such as carbon tax and energy efficiency standards on competitiveness across industries, as well as issues related to leakage, if any, of carbon-intensive industries to developing countries. Though competitiveness issues have been much debated in the context of carbon taxation policies, the study finds no evidence that industries' competitiveness is affected by carbon taxes. In fact, the analysis suggests that exports of most energy-intensive industries increase when a carbon tax is imposed by the exporting countries, or by both importing and exporting countries. This finding gives credence to the initial assumption that recycling the taxes back to the energy-intensive industries by means of subsidies and exemptions may be overcompensating for the disadvantage to those industries. There is, however, no conclusive evidence that supports relocation (leakage) of carbon-intensive industries to developing countries due to stringent climate change policies.